New records of gonodactylids (Crustacea: Stomatopoda: Gonodactylidae) from the Pacific Coast of Mexico with remarks on the morphology of Neogonodactylus lalibertadensis (Schmitt, 1940) - Salgado-Barragán, José; Hendrickx, Michel E.; Galván-Villa, Cristian M. (Zootaxa, 2013)
Eight species of the genus Neogonodactylus have been reported from the eastern Pacific. Up to now, only three of these species have been collected in Mexican waters: Neogonodactylus stanschi (Schmitt, 1940), N. lalibertadensis (Schmitt, 1940), and N. zacae (Manning, 1972). Recent sampling of stomatopods in several localities of the Pacific coast of Mexico, from Mazatlán, in the southwestern Gulf of California, to Oaxaca, allowed us to collect fresh material of these three spe-cies and five specimens that agree with the general description of N. lalibertadensis, but with differences in the telson or-namentation and the length of the ophthalmic somite. A close examination of this material and examination of photographs of the holotype led us to establish that it shows slight variation from the typical form. A revised key to the species of Neogonodactylus occurring in the eastern Pacific is provided.